Bernt Balchen papers - Balchen, Bernt, 1899-1973.; Balchen, Audrey S.; Balchen, Bernt, 1899-1973.; Kocivar, Ben.
Diaries; logbooks; autobiographical notes; research file of Balchen's wife, Audrey S. Balchen; scrapbooks; photographs; and other papers relating to Balchen's career in aviation and exploration. Documents his service as pilot on Richard Evelyn Byrd's 1927 transatlantic flight and on Antarctic expeditions with Byrd (1928-1930) and Lincoln Ellsworth (1933-1935); his World War II service with the U.S. Army Air Corps (later the Army Air Forces) including construction of an air base on Greenland and support for the Norwegian underground resistance movement; and his work with Norske luftfartselskap (Norwegian Airlines) in the 1930s and 1940s. Includes Balchen's log (1926) for the trimotor Josephine Ford; drafts of his autobiography, Come North with Me : An Autobiography (1958); and an interview with Balchen by Ben Kocivar.
Library of Congress Prints and Photographs Division.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Aviator, explorer, and U.S. Air Force officer. Born in Tveit, Norway; granted U.S. citizenship in 1929.
Collection material in English and Norwegian.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Byrd, Richard Evelyn, -- 1888-1957.; Ellsworth, Lincoln, -- 1880-1951.; United States. -- Army. -- Air Corps; United States. -- Army Air Forces; Josephine Ford (Trimotor); Norske luftfartselskap; Air bases -- Greenland; Transatlantic flights; World War, 1939-1945 -- Aerial operations; World War, 1939-1945 -- Underground movements -- Norway; Antarctica -- Discovery and exploration; Air Force officers; Aviators; Explorers